The SP19 chronology for the South Pole Ice Core – Part 1: volcanic matching and annual layer counting - D. A. Winski; T. J. Fudge; D. G. Ferris; E. C. Osterberg; J. M. Fegyveresi; J. Cole-Dai; Z. Thundercloud; T. S. Cox; K. J. Kreutz; N. Ortman; C. Buizert; J. Epifanio; et al. (Climate of the Past, 2019)
The South Pole Ice Core (SPICEcore) was drilled in 2014–2016 to provide a detailed multi-proxy archive of paleoclimate conditions in East Antarctica during the Holocene and late Pleistocene. Interpretation of these records requires an accurate depth–age relationship. Here, we present the SPICEcore (SP19) timescale for the age of the ice of SPICEcore. SP19 is synchronized to the WD2014 chronology from the West Antarctic Ice Sheet Divide (WAIS Divide) ice core using stratigraphic matching of 251 volcanic events. These events indicate an age of 54 302±519 BP (years before 1950) at the bottom of SPICEcore. Annual layers identified in sodium and magnesium ions to 11 341 BP were used to interpolate between stratigraphic volcanic tie points, yielding an annually resolved chronology through the Holocene. Estimated timescale uncertainty during the Holocene is less than 18 years relative to WD2014, with the exception of the interval between 1800 to 3100 BP when uncertainty estimates reach ±25 years due to widely spaced volcanic tie points. Prior to the Holocene, uncertainties remain within 124 years relative to WD2014. Results show an average Holocene accumulation rate of 7.4 cm yr −1 (water equivalent). The time variability of accumulation rate is consistent with expectations for steady-state ice flow through the modern spatial pattern of accumulation rate. Time variations in nitrate concentration, nitrate seasonal amplitude and δ 15 N of N 2 in turn are as expected for the accumulation rate variations. The highly variable yet well-constrained Holocene accumulation history at the site can help improve scientific understanding of deposition-sensitive climate proxies such as δ 15 N of N 2 and photolyzed chemical compounds.